New insights into the physiological role of carbonic anhydrase IX in tumour pH regulation. - Swietach, P; Hulikova, A; Vaughan-Jones, R; Harris, A (2010)
In this review, we discuss the role of the tumour-associated carbonic anhydrase isoform IX (CAIX) in the context of pH regulation. We summarise recent experimental findings on the effect of CAIX on cell growth and survival, and present a diffusion-reaction model to help in the assessment of CAIX function under physiological conditions. CAIX emerges as an important facilitator of acid diffusion and acid transport, helping to overcome large cell-to-capillary distances that are characteristic of solid tumours. The source of substrate for CAIX catalysis is likely to be CO₂, generated by adequately oxygenated mitochondria or from the titration of metabolic acids with HCO₃⁻ taken up from the extracellular milieu. The relative importance of these pathways will depend on oxygen and metabolite availability, the spatiotemporal patterns of the cell's exposure to hypoxia and on the regulation of metabolism by genes. This is now an important avenue for further investigation. The importance of CAIX in regulating tumour pH highlights the protein as a potential target for cancer therapy.